2004
DOI: 10.1128/aem.70.3.1413-1424.2004
|View full text |Cite
|
Sign up to set email alerts
|

PCR-Denaturing Gradient Gel Electrophoresis Profiling of Inter- and Intraspecies 18S rRNA Gene Sequence Heterogeneity Is an Accurate and Sensitive Method To Assess Species Diversity of Arbuscular Mycorrhizal Fungi of the GenusGigaspora

Abstract: Despite the importance of arbuscular mycorrhizal fungi in the majority of terrestrial ecosystems, their ecology, genetics, and evolution are poorly understood, partly due to difficulties associated with detecting and identifying species. We explored the inter-and intraspecies variations of the 18S rRNA genes of the genus Gigaspora to assess the use of this marker for the discrimination of Gigaspora isolates and of Gigasporaceae populations from environmental samples. Screening of 48 Gigaspora isolates by PCR-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 56 publications
2
45
0
1
Order By: Relevance
“…The PCR amplification tests with speciesspecific primers in this study also indicated that these two isolates should be reclassified as G. albida and G. rosea. Nevertheless recently Msiska & Morton Using PCR-DGGE analysis, Souza et al (2004) already observed, as we confirmed here, that the FL 927 isolate, originally identified as G. albida, should be ascribed to G. rosea, indicating identification problems. Endobacteria are usually observed in glomerospores of Gigaspora species, with the exception of G. rosea isolates.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The PCR amplification tests with speciesspecific primers in this study also indicated that these two isolates should be reclassified as G. albida and G. rosea. Nevertheless recently Msiska & Morton Using PCR-DGGE analysis, Souza et al (2004) already observed, as we confirmed here, that the FL 927 isolate, originally identified as G. albida, should be ascribed to G. rosea, indicating identification problems. Endobacteria are usually observed in glomerospores of Gigaspora species, with the exception of G. rosea isolates.…”
Section: Discussionsupporting
confidence: 61%
“…Due to the low morphological variation amongst Gigaspora species (Bentivenga & Morton 1995), some papers have reported species misidentification (Bago et al 1998, Souza et al 2004, Lanfranco et al 2001. These studies also report the usefulness of molecular approach as an identification tool.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Parasitized and degraded spores were removed during weekly checks. Intact spores were further cleaned by ultrasonication and rinsing (De Souza et al, 2004). Individual clean spores were collected and transferred to a 1.5 ml microcentrifuge tube (30-100 spores each) and stored at −80 °C until DNA extraction.…”
Section: Spore Extraction and Preparation For Dna Extractionmentioning
confidence: 99%
“…Kowalchuk et al (2002) was the first to apply DGGE to assess AMF diversity in sand dune soil and root samples. Other studies used DGGE to detect AMF in forest and grassland soil (Opik et al, 2003), agricultural ecosystems (Ma et al, 2005), and for the discrimination of AMF species (De Souza et al, 2004).…”
Section: Introductionmentioning
confidence: 99%